Genetic heterogeneity in the apolipoprotein C-III promoter and effects of insulin - Geesje M. Dallinga-Thie (Journal of Lipid Research, 2001)
In the present study, we have investigated the in vivo and in vitro role of two newly identified variants (G−944A and A−1180C) located in the upstream promoter region of the apolipoprotein C-III (apoC-III) gene. These variants were studied in 30 probands diagnosed with FCHL, their relatives, and spouses. The allele frequencies of both variants were not different between the groups. No significant associations between plasma lipid traits and DNA variants were observed. We further analyzed the effect of the presence of these variants in the upstream enhancing region of the apoC-III gene, as five different in vivo occurring haplotypes, on the transcriptional activity of apoC-III in both HepG2 and Caco-2 cells. All five promoter constructs, including the wild type, showed similar enhancing activity of the apoC-III gene. The average transcription efficiency was enhanced 19-fold in HepG2 cells and 11-fold in Caco-2 cells. Previous studies have shown in vitro insulin-dependent down-regulation of the apoC-III gene transcription in HepG2 cells by DNA variation in an insulin response element (IRE) in the apoC-III promoter. We observed a 30% insulin-dependent down-regulation of apoC-III expression that was, however, independent of the presence of the two IRE variants. In contrast, in Caco-2 cells, a more variable insulin-dependent up-regulation was found that was also independent of the presence of the IRE variants. In conclusion, our data suggested that the apoC-III gene transcription in vitro is regulated by insulin but independent of the presence of the two IRE variants at −455 and −482. We were unable to detect associations between these apoC-III variants and plasma lipids and insulin in our FCHL population. This means that in vivo apoC-III transcription not only depends upon insulin but appears to be mediated by other mechanisms. —Dallinga-Thie, G. M., M. Groenendijk, R. N. H. H. C. Blom, T. W. A. De Bruin, and E. De Kant. Genetic heterogenicity in the apolipoprotein C-III promoter and effects of insulin.